White Spot, a Novel Endoscopic Finding, May Be Associated with Acid-Suppressing Agents and Hypergastrinemia - Nishiyama, Noriko (J Clin Med, 2021)
White globe appearance (WGA) is defined as a microendoscopic white lesion with a globular shape underlying the gastric epithelium and is considered a marker of gastric cancer. We recently reported that endoscopically visualized white spot (WS) corresponding to WGA appeared on the nonatrophic mucosa of patients with acid-suppressing agents (A-SA) use. We evaluated patients undergoing routine esophagogastroduodenoscopy and divided the patients into an A-SA group (n = 112) and a control group (n = 158). We compared the presence of WS in both groups. We also compared WS-positive- (n = 31) and -negative (n = 43) groups within the A-SA group regarding these patients’ backgrounds and serum gastrin concentrations. Comparing the A-SA group with controls, the prevalence of WS was significantly higher (31/112 vs. 2/158; p < 0.001). The number of patients with high serum gastrin concentrations was significantly higher in the WS-positive group (18/31) vs. the WS-negative group (5/43) (p < 0.001). Within the A-SA group, the prevalence of WS was also significantly higher in patients taking potassium-competitive acid blockers vs. proton-pump inhibitors (21/31 vs. 10/31, p < 0.001). The WS-positive group had a significantly greater percentage of patients, with a high serum gastrin level (p < 0.001). WS may be associated with hypergastrinemia and potassium-competitive acid blockers.